Pengembangan Budidaya Kerapu Cantang (Epinephelus Sp) sebagai Alternatif Pendapatan Desa Lembung, Kecamatan Galis, Kabupaten Pamekasan - Zuliati, Zuliati; Widodo, Slamet; Zuhriyah, Amanatuz; Siwalette, Jeter Donald (Universitas Galuh, 2025)
The fisheries sector is one of the leading sectors in Indonesia that plays an important role in driving economic growth, as well as providing an impact on society. Aquaculture commodities that have a high chance of growing include grouper. Based on preliminary studies, there are challenges faced in grouper cultivation in Lembung Village, Galis District, Pamekasan Regency, namely fish growth that is not optimal and a high mortality rate of up to 64%. Therefore, this research has the following objectives: i) analyze the feasibility of grouper farming, and ii) formulate a strategy for developing grouper farming. Data analysis methods applied include: cost analysis, total revenue analysis, income analysis and R/C ratio, and SWOT analysis. The results explained that grouper farming can be an alternative source of income for salt farmers in the face of fluctuations in salt prices due to climate change. In addition, the R/C ratio value of 1.39 shows that this business is feasible to run with the profit obtained reaching Rp.16,931,001. Based on the results of the SWOT analysis, the difference between the X score of -0.30 and Y score of -0.11 is obtained, which places this business in quadrant IV, namely the W-T strategy. This strategy aims to minimize internal weaknesses and keep external threats away. Strategies that can be carried out are by providing adequate and balanced feed for fish and monitoring (W3, T3). Then improve the ability of human resources through training in grouper cultivation to increase knowledge and skills and overcome disease attacks on fish caused by parasites and pathogens (W1, W2, T1, T2, T3).